Leverage, Profitability, and Firm Size as Predictors of Financial Distress in Indonesian Textile Firms - Lana Iqlima; Maria Safitri; Stjepan Laća; Agus Prayitno; Dian Prawitasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the relationship between leverage, profitability, and company size on the possibility of financial distress of companies in the textile and garment industry listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. Several companies were selected using purposive sampling, based on categories determined by the author, such as the availability of data on each company and other relevant factors. The calculations used to analyze the financial difficulties of companies include the Altman Z-score and Zmijewski models, which will then serve as proxies for the dependent variable of financial distress. The results show that the relationship between the independent variables and the dependent variable differs between the models applied. The Altman Z-score model showed results that were more consistent with theoretical expectations, indicating a more robust measure of financial distress in this context. These findings highlight the importance of choosing appropriate models for analyzing financial distress in the textile and garment sector.